The Ontogeny of Somatic Embryos from in vitro Cultured Grapevine Anthers - Newton, D.J.; Goussard, P.G. (South African Journal of Enology and Viticulture, 2017)
Translucent light green to yellow anthers excised from Vitis rupestris cv. Rupestris du Lot flower buds, produced from cuttings grown in a climate-controlled room, produced somatic embryos when cultured on modified Nitsch & Nitsch (1969) medium supplemented with l μM 6-benzylaminopurine (BAP) and 5 μM 2,4-dichlorophenoxyacetic acid (2,4-D). Anatomical features of developing embryogenic explants were studied at various intervals, before and after the start of in vitro culture, using light microscopy. Results indicated that callus was entirely of somatic origin. Embryogenic cells were apparently present before in vitro culture commenced and multiplied sufficiently within the first 15 days' culture to form visible embryogenic growth centres. Embryogenic callus formed from the lateral and abaxial walls of the anther, all connective tissues and the filament. Somatic embryos were observed after 60 days of culture and possessed primordial vascular tissues and secondary embryoids. No vascular connections between somatic embryos were observed.